Comparison of throwing kinematics and muscle activation of female elite handball players with and without pain - the effect of repeated maximal throws - Piil Torabi, T.; Juul-Kristensen, B.; Dam, M.; Zebis, M. K.; van den Tillaar, R.; Bencke, J. (Sports Biomechanics, 2025)
Shoulder pain is common in team handball; however, many continue playing. The purpose was to investigate whether a functional fatigue protocol (FFP) containing repeated sub and maximal standing throws affects throwing performance, upper body kinematics, muscle peak activation (MPA) and whether the effect was different between the players playing with or with no pain. Thirty female elite handball players performed five maximal standing throws before and after the FFP. Throwing velocity, throwing kinematics, and MPA were measured before and after the FFP. An increased ball velocity (p = .02) was found, but only the total throwing time increased significantly in pain group (p = .05). Fatigue also resulted in a larger maximal pelvis (p = .03) and trunk rotation (p = .03) in addition to an increased shoulder flexion at ball release in both groups (p = .03), but only the maximal external (p = .03) and internal shoulder rotation (p = .05) increased in the pain group. Furthermore, fatigue also affected MPA in the latissimus dorsi (p = .02) and infraspinatus (p = .01). It was concluded that fatigue influenced throwing performance, kinematics, MPA and timing, which may increase the risk of developing non-traumatic shoulder injuries in team handball. The information may help to understand how fatigue influences throwing kinematics and MPA in players playing with pain.